Improving the Students’ Self-Confidence and Speaking Ability in the BIPA Class of Universitas PGRI Semarang through Video-Making Projects - Raden Yusuf Sidiq Budiawan (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study aims to improve student confidence and speaking skills in the BIPA University PGRI Semarang class through video making projects. This research is a qualitative descriptive study. The data were provided by interview, observation, and documentation. The data analyzed is carried out by collecting data, coding data, comparing data, constructing interpretations, and reporting results.  In addition, to overcome students 'problems, several attempts were made to increase students' confidence and speaking ability before making videos, such as doing role plays and simulations in class. After that, the students practice their speaking skills in real situations. The first cycle is making a video project around the City of Semarang, while the second cycle is carried out in the City of Magelang. This research data is presented by formal and informal methods. The results of the data analysis showed that the video making project was able to 1) significantly increase the student confidence and pronunciation; 2) improve the students' Indonesian language skills, especially fluency, vocabulary, and accuracy in grammar; and 3) increase their motivation and enthusiasm that encourage them to learn Indonesian in BIPA classes well.